PERAN AKHLAK SANTRI DALAM MENGHAFAL AL-QUR’AN DI MADRASAH ALIYAH MADRASATUL QUR`AN TEBUIRENG - Insanu AN; Ali Said; Muthi’ah Hijriyati (EL-Islam, 2019)
Al-Qur'an as the basic basis of Islamic education in it contains an absolute source of value, and the Qur'an as a role model for all Muslims, the book revealed to the prophet Muhammad SAW which is widely used as an example, especially in moral lessons such as the word Allah in the Surah Al Ahzab verse 21. Madrasah Aliyah Madrasatul Qur`an Tebuireng is one of the schools that applies the local tahfidz Qur`an curriculum (memorizing the Qur'an) each student is obliged to memorize the Qur'an with a specific target from the school. But the reality is that not all students who have the most memorized Al-Qur'an and have good character are memorized smoothly and conversely not all students whose morals are not good memorized smoothly. This phenomenon encourages researchers to examine and find out the role of the students' morals in improving the memorization of the Qur'an.